A területi különbségek hazai alakulásának kulcsmomentumai - Lengyel, Imre (Közép-Európai Közlemények, 2013)
Nowadays the investigation of the regional differences has become one of the major questions of regional science, generating vivid disputes about uneven territorial development. This study reviews the most important economic characteristics related to regional differences in Hungary. Facts show that the area around Budapest is still growing dynamically, well exceeding the EU-average, while other parts of the country are able to stagnate at best. Regional differences in the country are enormous, among the major ones in the EU. In my opinion the main problem of the increasing regional differences is the centralized top-down territorial development policy.